2015
DOI: 10.1080/20445911.2014.987676
|View full text |Cite
|
Sign up to set email alerts
|

Finding a link between guided search and perceptual load theory

Abstract: Perceptual load theory claims that attentional processing of distractors in the visual environment is dependent upon the availability of perceptual resources, and recent research has attempted to link this selective attention theory to more classic ideas on visual search. In the present study, we investigated how perceptual load could be linked to a prominent visual search theory: guided search. Our findings suggest that any volitional attempt at attentional guidance only hindered attention under low perceptua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 61 publications
1
17
1
Order By: Relevance
“…A further example of attentional enhancement of distractor stimuli under conditions in which resources had been depleted by a perceptually demanding task was provided by Biggs et al (2015). They found that guided search was effective under high, but not low, load conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A further example of attentional enhancement of distractor stimuli under conditions in which resources had been depleted by a perceptually demanding task was provided by Biggs et al (2015). They found that guided search was effective under high, but not low, load conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of work has shown that colour as a feature will capture attention if it is a distractor (e.g. Snowden, 2002;Theeuwes, 1992Theeuwes, , 1994 or guide attention if it is a target (Biggs et al, 2015;Eimer and Grubert, 2014;Eimer and Kiss, 2010;Folk et al, 1994;Grubert and Eimer, 2015;Müller et al, 2009;Nordfang et al, 2013;Wolfe, 2007;Wolfe et al, 1989;Wolfe andHorowitz, 2004, 2017). For example, Theeuwes (1992) asked participants to search for lines embedded in a green circle amongst green squares, or green squares with a singleton red square.…”
Section: Attentional Guidance Of Colourmentioning
confidence: 99%
“…The importance of colour in visual design is corroborated by its importance in experimental psychology, where colour has been shown to reliably bias our attention, meaning that search is facilitated for coloured targets and that attention is more easily captured by coloured distractors (Biggs et al, 2015;Eimer and Grubert, 2014;Eimer and Kiss, 2010;Folk et al, 1994;Grubert and Eimer, 2015;Muhl-Richardson et al, 2018;Müller et al, 2009;Nordfang et al, 2013;Theeuwes, 1994;Wolfe andHorowitz, 2017, 2004). Notably, whereas the aforementioned applied studies mostly consider how visual designs of various colour combinations perform, the experimental studies of colour and attention mostly consider colour as a group (i.e.…”
Section: Introductionmentioning
confidence: 96%
“…These results prompted Roper et al to propose that PL is a continuous variable better defined operationally by search efficiency rather than task difficulty. (See also Biggs et al, 2015, for evidence on the interaction between visual search and PL.) Chen and Cave (2013) went even further in controlling salience.…”
Section: Dilutionmentioning
confidence: 99%
“…A distractor or nontargets that are in the same hemisphere as the target will reduce distractor processing compared to a distractor or nontargets in different hemispheres (Torralbo & Beck, 2008;Wei, Kang, & Zhou, 2013). An infrequently presented onset distractor leads to significant distraction processing while a frequently presented one does not (Cosman & Vecera, 2010), and both perceptual grouping and the salience of a target relative to the distractor and/or the other stimuli in a display affect the degree of distractor processing (Baylis & Driver, 1992;Biggs & Gibson, 2013;Biggs, Kreager, & Davoli, 2015;Eltiti, Wallas, & Fox, 2005;Yeh & Lin, 2013;Yeshurun & Marciano, 2013). These and other empirical findings Biggs & Gibson, 2010;Chen & Chan, 2007;Wilson et al, 2011;Yeh, Lee, Chen, & Chen, 2014 ), together with the conceptual and methodological issues raised by a number of researchers (see Benoni & Tsal, 2013;Giesbrecht, Sy, Bundesen, & Kyllingsbaek, 2014;and Murphy, Groeger, & Greene, 2016, for reviews), indicate that the simple principles of PLT do not fully capture the complex interactions among targets and nontargets in complex stimulus arrays.…”
Section: Perceptual Loadmentioning
confidence: 99%